Microbial synthesis of medium-chain chemicals from renewables - Sarria, Stephen; Kruyer, Nicholas S; Peralta-Yahya, Pamela (Nature biotechnology, 2017)
Strategies to engineer microorganisms to produce medium-chain hydrocarbon chemicals are reviewed. Linear, medium-chain (C8–C12) hydrocarbons are important components of fuels as well as commodity and specialty chemicals. As industrial microbes do not contain pathways to produce medium-chain chemicals, approaches such as overexpression of endogenous enzymes or deletion of competing pathways are not available to the metabolic engineer; instead, fatty acid synthesis and reversed β-oxidation are manipulated to synthesize medium-chain chemical precursors. Even so, chain lengths remain difficult to control, which means that purification must be used to obtain the desired products, titers of which are typically low and rarely exceed milligrams per liter. By engineering the substrate specificity and activity of the pathway enzymes that generate the fatty acyl intermediates and chain-tailoring enzymes, researchers can boost the type and yield of medium-chain chemicals. Development of technologies to both manipulate chain-tailoring enzymes and to assay for products promises to enable the generation of g/L yields of medium-chain chemicals.